Epidemiology and outcomes of gastroparesis, as documented in general practice records, in the United Kingdom. Issue 4 (3rd June 2020) - Ye, Yizhou; Jiang, Baoguo; Manne, Sudhakar; Moses, Peter L; Almansa, Cristina; Bennett, Dimitri; Dolin, Paul; Ford, Alexander C
Abstract : Objective: To generate real-world evidence for the epidemiology of gastroparesis in the UK, we evaluated the prevalence, incidence, patient characteristics and outcomes of gastroparesis in the Clinical Practice Research Datalink (CPRD) database. Design: This was a retrospective, cross-sectional study. Prevalence and incidence of gastroparesis were evaluated in the CPRD database, with linkage to Hospital Episodes Statistics Admitted Patient Care and Office for National Statistics mortality data. Prevalence and incidence were age and sex standardised to mid-2017 UK population estimates. Descriptive analyses of demographics, aetiologies, pharmacological therapies and mortality were conducted. Results: Standardised prevalence of gastroparesis, as documented in general practice records, was 13.8 (95% CI 12.6 to 15.1) per 100 000 persons in 2016, and standardised incidence of gastroparesis rose from 1.5 (95% CI 1.1 to 1.8) per 100 000 person-years in 2004 to 1.9 (95% CI 1.4 to 2.3) per 100 000 person-years in 2016. The most common disease aetiologies were idiopathic (39.4%) and diabetic gastroparesis (37.5%), with a similar distribution of type 1 and type 2 diabetes among the 90% who had type of diabetes documented. Patients with diabetic gastroparesis had a significantly higher risk of mortality than those with idiopathic gastroparesis after diagnosis (adjusted HR 1.9, 95% CI 1.2 to 3.0). Of those with gastroparesis, 31.6% were not offered any recognised pharmacological therapy after diagnosis. Conclusion: This is, to our knowledge, the first population-based study providing data on epidemiology and outcomes of gastroparesis in Europe. Further research is required to fully understand the factors influencing outcomes and survival of patients with gastroparesis.